From Phantoms to Prostheses - Cohen, Emily (Disability Studies Quarterly, 2012)
Colombia, a country at war for over fifty years, has one of the highest rates of landmine injuries in the world. For decades, landmine victims have remained outside the nation’s popular consciousness. Today, landmines and rehabilitative medicine profoundly shape public life. This article shows how the seemingly mundane activity of walking becomes a strangely familiar experience among amputees and an increasingly technical one among medical practitioners in Colombian rehab units. It’s worth noting that when patients and medical staff discussed how they or their patients learned how to walk using prostheses, they also often talked about their experiences with phantom limbs. As subjective as bodily sensations are I argue that they are nonetheless implicated in social relations of power and political and economic change. Within rehab medicine, clinicians frequently see phantoms as part of a patient’s healing process and sometimes worry that failing to experience the amputated limb as a felt presence makes recovery more difficult. Without a missing object, there is no object to desire, they presume. Rather than treat phantom limb sensation as a kind of psychosis, this essay explores how the Colombian medical establishment talks about rehabilitation with prostheses as a form of social, physical, and psychological integration. I also show how patients, meanwhile, experience a kind of ambivalence—marked by oscillating feelings of strangeness and naturalness—regarding limb loss and the prostheses they use to manage it. Keywords: phantom sensation, limb loss, rehabilitation, Colombia, war